OPTIMIZING THE CREATIVE ECONOMY IN INDONESIA: THE LEGAL INTEGRATION OF VILLAGE-OWNED ENTERPRISES AND MICRO, SMALL, AND MEDIUM ENTERPRISES - Dora Kusumastuti; Yenny Febrianty; Ade Sathya Sanathana Ishwara; Masitah Pohan (Universitas Syiah Kuala, 2023)
The concept of the creative economy revolves around fostering community participation and developing the micro, small, and medium enterprise (MSME) sector. This orientation is closely linked to the presence of Village-Owned Enterprises (BUMDes) institutions. However, legal challenges arise when separate regulations govern MSMEs and BUMDes, hindering the optimization of the creative economy within society. This article aims to address these legal issues by examining the integration of BUMDes and MSMEs to enhance the creative economy in Indonesia. Drawing on normative research, this article takes a conceptual and statutory approach to shed light on the matter. The findings affirm the need for specific legal policies that facilitate the integration of MSMEs and BUMDes, enabling them to collaborate and regulate their potential collectively. Special regulations should be established to govern the various aspects of integration, including the forms of integration, the fields that can be integrated, and the legal processes involved in developing the creative economy. By establishing comprehensive regulations, Indonesia can foster a conducive environment for the creative economy to thrive, promoting collaboration between MSMEs and BUMDes while harnessing their potential for societal development.